Rekonstruksi Teks-Teks Hukum Qath i dan Teks-Teks Hukum Zhanni (Meretas Jalan Menuju Pendekatan Tekstual-Kontekstual) - Laode Ismail Ahmad; Syamsidar Syamsidar (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2015)
This paper examines the issue of qath'i and zhanni in the realm of Islamic legal thought with regard to source of truth (wurud) and an indication of the law (dalalah). Terms qath'i and zhanni often associated with the position of the Qur'an and Sunnah judging from the aspect of al-tsubut or al-wurud (truth source/ constancy) and al- dalalah (meaning the content/ legal indications). This is done in an attempt to formulate and define the 'region' of Islam which can not be carried ijtihad. As the product ijtihadi, qath'i and zhanni only bore deviation among jurists in the level of assessment of whether a definitive text in the qathi or zhanni. Therefore, reconstruction of discourse qath'i zhanni a necessity to give a theory that qath'i zhanni only in the realm of constancy (wurud), whereas in the realm dalalah (legal indications ) no definitive, only zhanni.